2013
DOI: 10.3390/molecules18067279
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Reactions Catalyzed by Metalloporphyrin-Based Metal-Organic Frameworks

Abstract: Abstract:The synthetic versatility and the potential application of metalloporphyrins (MP) in different fields have aroused researchers' interest in studying these complexes, in an attempt to mimic biological systems such as cytochrome P-450. Over the last 40 years, synthetic MPs have been mainly used as catalysts for homogeneous or heterogeneous chemical reactions. To employ them in heterogeneous catalysis, chemists have prepared new MP-based solids by immobilizing MP onto rigid inorganic supports, a strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 133 publications
0
63
0
1
Order By: Relevance
“…The epoxidation of alkenes is one of the processes of great importance in the fine chemical industry from an economic point of view, because epoxides are useful intermediates in the production and manufacture of high-value commercial polymers like polyurethane, polyamides, resins, and polyesters [31]. In addition, this transformation is used to carry out bioinspired oxidations [32] to produce drug candidates or metabolites (Scheme 3).…”
Section: Epoxidationmentioning
confidence: 99%
“…The epoxidation of alkenes is one of the processes of great importance in the fine chemical industry from an economic point of view, because epoxides are useful intermediates in the production and manufacture of high-value commercial polymers like polyurethane, polyamides, resins, and polyesters [31]. In addition, this transformation is used to carry out bioinspired oxidations [32] to produce drug candidates or metabolites (Scheme 3).…”
Section: Epoxidationmentioning
confidence: 99%
“…18 Accordingly, metalloporphyrinic materials can reproduce the natural functions of porphyrins and move them to molecular level structured systems and nanotechnological devices. 19,20 In this sense, porphyrin-based MOFs are reporting great results, [21][22][23] since Suslick et al reported the first catalytic activity of a porphyrinic coordination polymer with open structure. 24 In the last years, porphyrinic complexes of iron, 25 cobalt, 26 ruthenium, 27 rhodium, 28 among others, are known in literature to catalyze chemical reactions like, for example, olefin cyclopropanation and X-H (X = C, N, Si) bond insertion with high efficiency and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, the free-base porphyrin P2 afforded the corresponding complexes FeP2 and MnP2 (Figure 2), which were soluble in most organic solvents A c c e p t e d M a n u s c r i p t MOFs are solids that originate from binding between organic or inorganic molecules and metal clusters, which results in a robust and often nanoporous bi-or tridimensional supramolecular structure [12,54]. Supramolecular systems based on porphyrins can display various kinds of interactions: a ligand group can interconnect the macrocycles (van der Waals interactions), or one donor atom present in the metalloporphyrin can bind to the metal center of another metalloporphyrin [12].…”
Section: Preparation Of Manganese Iron and Copper Porphyrins (Mpx)mentioning
confidence: 79%
“…This absence of signal was observed for the MnP2 EPR analysis but nevertheless, as described in the previous paragraph, an EPR signal emerged at g = 2.0 ( Figure S17) for the solid MnP6, which could refer to the existence of Mn(II) ions that probably acted as coordinative ions for the peripheral acid groups present in the ring of porphyrin P6. This coordination should generate and stabilize the structured solid MnP6 [12].…”
Section: Page 18 Of 49mentioning
confidence: 97%